1986
DOI: 10.1007/bf00508649
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A, B and C immunoreactivities of mammalian endocrine cells

Abstract: Antibodies specific for chromogranin A, B or C have been used to detect immunohistochemically these three anionic proteins. Pancreatic A, B and PP cells, gut argentaffin EC, argyrophil ECL and gastrin G cells, thyroid C cells, parathyroid cells, adrenal medullary cells, pituitary TSH, FSH and LH cells as well as some axons of visceral nerves have been found to react with chromogranin A antibodies. Pancreatic A, gut EC and G, adrenal medullary and pituitary cells as well as some gut nerve fibers showed chromogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Confirming previous findings our study showed that gastrin, CgA, and CgB immunoreactivities colocalized in identical G-cells (17,18,27); typically, these immunoreactivities varied markedly within the G-cell population. Basically, two reasons may explain the intercellular variations of immunoreactivities in a given tissue section: (i) existence of molec- ular variants (precursor forms and breakdown products) of gastrin, CgA, and CgB that crossreact differently with the corresponding antiserum; (ii) intercellular differences in the amount of gastrin, CgA, and CgB.…”
Section: Discussionsupporting
confidence: 91%
“…Confirming previous findings our study showed that gastrin, CgA, and CgB immunoreactivities colocalized in identical G-cells (17,18,27); typically, these immunoreactivities varied markedly within the G-cell population. Basically, two reasons may explain the intercellular variations of immunoreactivities in a given tissue section: (i) existence of molec- ular variants (precursor forms and breakdown products) of gastrin, CgA, and CgB that crossreact differently with the corresponding antiserum; (ii) intercellular differences in the amount of gastrin, CgA, and CgB.…”
Section: Discussionsupporting
confidence: 91%
“…The relatively poor affinity for histamine of VMAT2 may not be critical in the histamine-rich ECL which, at least in rats, is essentially devoid of serotonin and catecholamines (Hakanson, 1970;Rubin & Schwartz, 1983, 1984 (Dimaline & Sandvik, 1991;Swarovsky et al 1994). In addition, we observed a twofold increase in the mRNA encoding CGA, which is located in rat ECL cells (Rindi, Buffa, Sessa, Tortora & Solcia, 1986;Grube, Bargsten, Cetin & Yoshie, 1989) and which is thought to play a role in the formation and stabilization of secretory granules (Wiedenmann & Huttner, 1989;Helle, 1990 …”
Section: Discussionmentioning
confidence: 76%
“…synaptophysin and chromogranin A, which are components of small synaptic-like vesicles, and large dense-core vesicles, respectively (Rindi et al 1986, Wiedenmann et al 1986). Furthermore, GEPNETs are derived from progenitor cells in the intestinal crypts or pancreatic ducts, and consequently express epithelial markers, e.g.…”
Section: Discussionmentioning
confidence: 99%